Inside the artist's studio - Fig, Joe (New York, New York Princeton Architectural Press, 2015)
What was your earliest childhood artwork that received recognition? When did you first consider yourself a professional artist? How has your studio's location influenced your work? How do you choose titles? Do you have a favorite color?Joe Fig asked a wide range of celebrated artists these and many other questions during the illuminating studio visits documented in Inside the Artist's Studio—the follow-up to his acclaimed 2009 book, Inside the Painter's Studio. In this remarkable collection, twenty-four painters, video and mixed-media artists, sculptors, and photographers reveal highly idiosyncratic production tools and techniques, as well as quotidian habits and strategies for getting work done: the music they listen to; the hours they keep; and the relationships with gallerists and curators, friends, family, and fellow artists that sustain them outside the studio.
Keywords: Artists' studios in art; Art, American -- 21st century; Artists -- United States -- Interviews